An Analysis of Conceptual Metaphor in the Poems Entitled “Classic Poetry Series” by William Blake - Fingky Sinthya; Dahnilsyah Dahnilsyah; Erni Erni (Institut Agama Islam Negeri Palopo, 2022)
This research aims to analyze the types of metaphors used and contained meanings contained in a collection of poems by William Blake. A metaphor is a part of figurative language that compares one thing to another. The researcher used a descriptive employed in study qualitative method to identify a collection of classic poetry by William Blake. The researcher uses the theory of Lakoff, George, and Johnsen (2003) to analyze the conceptual metaphors that shape the reality of 'life' which is reflected in poetry. There are three steps in collecting research data: observation, selection, and classification. This research result shows that ninety-five metaphorical lyrics are contained in the ten of classic collections of poetry by William Blake. The data were gathered using a collection of poems from three types of conceptual metaphors: structural, orientational, and ontological. The types of metaphors found in this research are ontological metaphors. And in reverse, the meaning of each metaphor depends on the type used in the poem. In conclusion, the poems by William Blake have a high imagination based on experiences as well as advice to the readers.